Benefits on body fat composition of isocalorically controlled diets including functionally optimized meat products: Role of alpha-linolenic acid. (January 2015) - Navas-Carretero, Santiago; San-Cristobal, Rodrigo; Avellaneda, Antonio; Planes, Jose; Zulet, M. Angeles; Martínez, J. Alfredo
Highlights: Optimized meat products higher in n-3 PUFA content may be a feasible healthy strategy. ALA consumption may play a role in body weight management within an isocaloric diet. Meat products can be devised to reduce saturated fat and increased n-3 supply. Abstract: The effects on body composition and cardiovascular risk of functional meat products, within a balanced diet, were investigated in a randomized, double-blind, 10-week nutritional intervention. Fifty-four adults were distributed in three groups, consuming 600 g/week of a reference meat product (RP), optimized nutritional product-1 (ONP-1), lower in fat, or ONP-2, n-3 PUFA enriched. Measures were performed at baseline and the endpoint. All groups lost fat mass, being subjects on the ONP-2 group those with more fat loss (p = 0.042) compared to the other groups. Correlation analyses evidenced significant associations between alpha-linolenic acid (ALA) intake and plasma levels (p = 0.001), as well as between plasma levels and fat mass changes (p = 0.03). The inclusion of optimized meat products, with n-3 PUFA (Polyunsaturated fatty acids) and an improved nutritional profile may be a healthy strategy, as a functional food, within an isocalorically controlled diet. ALA consumption may play a role in body composition changes.